Effect of cognitive behavioral active engagement training on test item construction skills among primary school teachers in Nigeria: Implication for educational policy makers. Issue 36 (10th September 2021) - Ede, Moses Onyemaechi; Agah, John J.; Okeke, Chinedu Ifedi; Chuks, Zudonu Onisoman; Oguguo, Basil C.E.; Agu, Patricia Uzoamaka; Ene, Catherine U.; Ekesionye, Ngozi E.; Nji, Ifeyinwa Awele; Eze, Chikodili; Manafa, Ifeyinwa F.
Abstract: Background: Most classroom teachers are weak in constructing test items for assessment of students. This study examined the effects of cognitive behavioral active engagement training on test items construction skills among primary school teachers in Nigeria. Methods: We adopted a randomized pretest–posttest control group design. A total of 148 participants served as the study sample. One instrument was used for data collection. The participants were administered the instrument at 4 different times. Test construction guide was employed to implement the training. Data analysis was completed using analysis of covariance. Results: The researchers found that cognitive behavioral active engagement training had a significant effect on participants' test items construction scores as measured by test construction skills inventory at posttest, first and second follow-up stages. Conclusion: The researchers concluded that cognitive behavioral active engagement training is efficacious in the improvement of test items construction skills among primary school teachers in Nigeria.